Understanding clinical expertise: Nurse education, experience, and the hospital context - McHugh, Matthew D.; Lake, Eileen T. (Research in nursing & health, 2010)
Clinical nursing expertise is central to quality patient care. Research on factors that contribute to expertise has focused largely on individual nurse characteristics to the exclusion of contextual factors. To address this, we examined effects of hospital contextual factors and individual nurse education and experience on clinical nursing expertise in a cross‐sectional analysis of data from 8,611 registered nurses. In a generalized ordered logistic regression analysis, the composition of the hospital staff, particularly the proportion of nurses with at least a bachelor of science in nursing degree, was associated with significantly greater odds of a nurse reporting a more advanced expertise level. Our findings suggest that, controlling for individual characteristics, the hospital context significantly influences clinical nursing expertise. © 2010 Wiley Periodicals, Inc. Res Nurs Health 33:276–287, 2010